1999
DOI: 10.1046/j.1365-2745.1999.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The genesis of two Picea–Cladina forests in northern Sweden

Abstract: Summary1 In northern Fennoscandia a rare forest type, characterized by Cladina species and Picea abies, occurs on dry productive sites outside the range of permafrost but close to the Scandes mountains. 2 We determined the history of vegetation development and disturbance of two Picea±Cladina forests to test the hypothesis that this forest type has a natural origin.3 We used a combination of several retrospective vegetation history and archaeological methods, i.e. the analysis of pollen, macroscopic charcoal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Henry and Swan 1974, Hörnberg et al 1999, Moore et al 1999, Motzkin et al 1999, Swetnam et al 1999, Dey and Guyette 2000, Ericsson et al 2000, Axelsson 2001. Although human impact is difficult to measure adequately (Östlund 1999), the historical knowledge gained is a prerequisite for nature conservation, restoration and forest management aimed at maintaining biological diversity in forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Henry and Swan 1974, Hörnberg et al 1999, Moore et al 1999, Motzkin et al 1999, Swetnam et al 1999, Dey and Guyette 2000, Ericsson et al 2000, Axelsson 2001. Although human impact is difficult to measure adequately (Östlund 1999), the historical knowledge gained is a prerequisite for nature conservation, restoration and forest management aimed at maintaining biological diversity in forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…as having very limited or no human impact. However, an increasing body of evidence indicates that human land use in sub-alpine Scandinavian forests has had a substantially longer history and more profound effects on forest structure, ecological processes and ecosystem function than previously acknowledged (Hicks 1995, Hörnberg et al 1999, Karlsson et al 2009, Josefsson et al 2010b). Furthermore, previous studies have shown that effects of past land use can reverberate through ecosystems for many centuries, and be almost imperceptible to the human eye at present (Foster et al 2003.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…However, people have clearly utilized forests in northern Scandinavia for thousands of years (Bergman et al 2003), at varying intensities and spatial scales (Hörnberg et al 1999, Hellberg et al 2004, Josefsson et al 2010b). Landuse intensity has increased or decreased rather abruptly in response to changes in climate and other external factors.…”
Section: Implications For Sampling Strategies In Dendroclimatologicalmentioning
confidence: 99%
“…When trying to explain the patterns we found, it is important to note that previous cutting operations have strongly influenced the forests that we can study today. Logging (also in a local context) was not performed randomly and may have influenced certain areas more strongly than others (Ostlund et al 1997;H6rnberg et al 1999). Previous influences of forest fires were also an important non random mortality factor for Scots pine in the landscape during the studied period (Zackrisson 1977;Engelmark 1984).…”
Section: Distribution Patternsmentioning
confidence: 99%